Spatial and temporal distribution patterns and factors influencing hepatitis B in China: a geo-epidemiological study - Kang Fang; Na Cheng; Chuang Nie; Wentao Song; Yunkang Zhao; Jie Pan; Qi Yin; Jiwei Zheng; Qinglin Chen; Tianxin Xiang (BMC Public Health)
Abstract Background China is a country with an extremely high disease burden of hepatitis B. Spatiotemporal analysis of hepatitis B from a socioeconomic perspective is of great significance for reducing the disease burden, but there is still a relative lack of research. Methods The age-period-cohort model and spatial distribution maps describe the three-dimensional distribution characteristics of hepatitis B. Spatial autocorrelation analysis and spatiotemporal scanning were used to analyze the spatiotemporal distribution characteristics. The random forest algorithm was used to screen the potential influencing factors. The geographic detector model was used to analyze the interaction patterns of variables. Finally, a geographically and temporally weighted regression model was established to analyze the effects of variables on the incidence rate of hepatitis B at different spatiotemporal scales. Results From 2004 to 2023, a total of 20,376,898 cases of hepatitis B were reported in China. The incidence rate of hepatitis B decreased at a rate of 3.31% per year, and hepatitis B vaccination has led to this downward trend, accompanied by a significant birth cohort effect. And it shows an aggregated characteristic, which highlights the inequality of geographical distribution. Stronger explanations for the incidence of hepatitis B were found for the number of people at the end of each year (q = 0.1949; where q value refers to the explanatory ability of the independent variable for the dependent variable) and the proportion of rural population (q = 0.1895), with an even stronger explanation for the interaction (q = 0.5366). The magnitude and direction of the effect of factors influencing hepatitis B also varied in different regions, and the effect of each factor on the incidence of hepatitis B was not an independent event. Conclusions The later people are born, the lower the incidence of hepatitis B. The northwest and southwest regions are the main hotspots, but there is a tendency to spread to southern China. The number of beds in medical institutions should be increased in densely populated areas, and economic development should be accelerated in sparsely populated areas. Hepatitis B prevention and control should be prioritized in geographic hotspots, coupled with enhanced awareness campaigns in rural areas and catch-up vaccination programs targeting high-risk populations.